2015
DOI: 10.1007/s12036-015-9329-x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Precursors of Flares in Active Region NOAA 10486

Abstract: Four different methods are applied here to study the precursors of flare activity in the Active Region NOAA 10486. Two approaches track the temporal behaviour of suitably chosen features (one, the weighted horizontal gradient W G M , is generalised form the horizontal gradient of the magnetic field, G M ; another is the sum of the horizontal gradient of the magnetic field, G S , for all sunspot pairs). W G M is a photospheric indicator that is a proxy measure of magnetic non-potentiality of a specific area of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
2
5
0
1
Order By: Relevance
“…Magnetographic studies of AR 12242 showed that, during the development of the group, opposite polarity fields converged in the AR and strong gradients were formed near the neutral line, i.e., two days before the flare, a so-called it SHIL (strong-field, high-gradient polarity inversion line) formed in the AR that is now recognized by many researchers as the clearest AR precursor for a large flare The study of the evolution of the total gradient (flare index) of AR 12242 showed that, before the X-flare, the index first increased and then, after the maximum was passed (20 h before the flare), decreased before the X flare. Note that a similar conclusion was made by Korsos et al (2014Korsos et al ( , 2015, who analyzed the parameters of sunspot groups in a number of flare regions and found that there is usually a sharp increase in the magnetic field gradient before large flares that reaches a high maximum, followed by its decrease just before the flare.…”
Section: Discussionsupporting
confidence: 74%
“…Magnetographic studies of AR 12242 showed that, during the development of the group, opposite polarity fields converged in the AR and strong gradients were formed near the neutral line, i.e., two days before the flare, a so-called it SHIL (strong-field, high-gradient polarity inversion line) formed in the AR that is now recognized by many researchers as the clearest AR precursor for a large flare The study of the evolution of the total gradient (flare index) of AR 12242 showed that, before the X-flare, the index first increased and then, after the maximum was passed (20 h before the flare), decreased before the X flare. Note that a similar conclusion was made by Korsos et al (2014Korsos et al ( , 2015, who analyzed the parameters of sunspot groups in a number of flare regions and found that there is usually a sharp increase in the magnetic field gradient before large flares that reaches a high maximum, followed by its decrease just before the flare.…”
Section: Discussionsupporting
confidence: 74%
“…In conclusion, the inherent plasma and magnetic field changes and the similar changes in the ambient corona may lead the dynamics and instability of the solar magnetic flux ropes. In spite of that, some canonical processes may also subject in making the magnetic flux ropes unstable (Török & Kleim 2005;Srivastava et al 2010;Cheng et al 2014b;Korsós, Baranyi, & Ludmány 2014;Korsós et al 2015, and references cited there). Better understanding the physics of solar magnetic flux ropes: their formation, identification, stability, and instability conditions are of great importance in solar and heliospheric physics as they are the precursor of huge coronal mass ejections and geomagnetic storms.…”
Section: Discussionmentioning
confidence: 99%
“…[9]. Аналогичный характер изменения расстояния между областями максимальных магнитных полей противоположных полярностей обнаружен и другими авторами [5] и может быть объяснен моделью магнитного жгута, зажатого между двумя сближающимися магнитными центрами (пятнами), согласно которой сначала сближение пятен обеспечивает накопление свободной магнитной энергии в жгуте, а затем, при расхождении пятен, в нем начинается вспышечное энерговыделение [6,7]. Выявленные свойства микроволнового излучения (резкое возрастание интенсивности, увеличение наклона спектра, уменьшение степени поляризации на 3 см) позволяют предположить, что 4 сентября в АО развился NLSисточник [1], который может рассматриваться как предвестник больших вспышек.…”
Section: рисunclassified